Three new species of Luciogobius Gill (Teleostei: Gobiidae) from Taiwan - Chen, I-Shiung; Ren, Yu-Ting; Jiang, Guo-Chen; Wang, Shen-Chih; Chang, Chih-Wei (Zootaxa, 2024)
Three new species of gobiid fish of Luciogobius Gill, 1859 have been recently discovered in Taiwan. Luciogobius chiaojinensis sp. nov. is found and collected mainly from Keelung, northern Taiwan. It can be distinguished from other congeneric species by the following combination of features: (1) second dorsal fin rays: I/10 and anal fin rays I/11; (2) pectoral fin rays modally 13 and with one upper, short free soft ray; (3) vertebral count: 20 + 21 = 41; and (4) specific coloration: head and body with small tiny blackish brown spots. Head with densely-set small blackish brown spots in male; second dorsal fin brown and darker on lower half; pectoral fin base on upper 1/2 region with round melanophores; and pectoral fin membrane mostly spotless. Luciogobius huatungensis sp. nov. is found and collected mainly from Hualien and Taitung Counties in eastern Taiwan. It can be well distinguished from other congeneric species by the following combination of features: (1) second dorsal fin modally I/15 and anal fin I/15; (2) pectoral fin rays 14 and with 4 upper, free soft rays and 1 lower free rays; (3) vertebral count: 17 + 22 = 39; and (4) specific coloration: body brown with minute creamy yellow round spots; head and body with small brown spots; belly creamy yellow with fewer brown spots; second dorsal fin with tiny white marks; and pectoral fin with several round melanophores, most membrane with brown marks. Luciogobius newtaipeiensis sp. nov. is found and collected mainly from New Taipei City in northern Taiwan. It can be well distinguished from other congeneric species by the following combination of features: (1) second dorsal fin rays: I/11 and anal fin rays I/12; (2) pectoral fin rays modally 18 and with 1 upper free soft ray; (3) vertebral count: 16 + 20 = 36; (4) a dermal projection on posterior part of eye; and (5) specific coloration: head and body with small tiny brownish black spots; second dorsal rays light brown; and pectoral fin base with many small melanophores, fin membrane with melanophores on basal region. A diagnostic key for all six nominal species of Taiwan and the Matsu Islands will be provided in this paper.